Optimized Energy Efficient and QoS Aware Routing Protocol for WBAN - Kaur, Tejinder; Kaur, Navneet; Sidhu, Gurleen (Recent Patents on Engineering, 2020)
The expansion of an average lifetime and increased cost of health analysis have resulted in effective methods for healthcare monitoring. A Wireless Body Area Network (WBAN) is used for continuous monitoring of patients to enhance health care and quality of life. As the sensors worn on the human body have a small size, low transmission power and restricted battery, which necessitate the development of energy-efficient routing protocols for increasing the network lifetime. This paper proposes an Optimized Energy Efficient and Quality-of-Service aware Routing Protocol (OEEQR) to achieve longer network lifetime, energy efficiency, lower delay and high throughput. In the proposed protocol, the cost function with residual energy, distance and path loss as its parameters is optimized using Particle Swarm Optimization (PSO) technique. The proposed cost function determines the best feasible next hop to send the data to the sink.
Keywords: Wireless body area network